The Prophet Educates Children Without Violence - Mudaris, Hudan; Musaropah, Umi; Supriyanto, Agus; Widiyastuti, Anik; Nasrudin, Muhammad (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
This paper intends to explore the hadith on the method of educating children to formulate important points in instilling anti-violence ideas to school. The exploration is limited to the text of the hadiths narrated in the kutus tis'ah to be analyzed through content analysis. In the hadith, the method of Islamic religious education emphasizes empathetic interaction to be felt as a necessity in anti-violence education . This role model can be deliberate to act consciously imitated by the children. Another form is behavior in accordance with the values ​​and norms that will be instilled in children so that they unintentionally become role models for children. All can be adapted in school outside the family by considering the factors of the giver, recipient, material and context.